Strategy for the Principal’s Transformational Leadership Approach in Strengthening the Character of Indonesian Students - Rustan Effendi, Yulius (Pedagogika, 2023)
This study endorses cultural, humanistic, and nationalistic approaches for principals’ transformational leadership, outlining character development across three frameworks. It uses qualitative methods (interviews, observation, document review), analyzed with modified analytic analysis. Findings strongly favor principals adopting these approaches, significantly enhancing student character development. Indonesian principals should prioritize cultural values, spirituality, and nationalism for inclusive, character-nurturing schools.